Current economic position and prospects of jamaica 1963 - International Bank for Reconstruction and Development (Jamaica: International Bank for Reconstruction and Development, 1963)
This book portrayed the current economic position and prospects of Jamaica 1963 prepared by the International Bank for Reconstruction and Development.
rpm 18/02/2019
Ref
Keywords: Economic Position; Economic Prospects; Jaimaca